Performance enhancement of a flat tubular geometric design in indirect evaporative cooling systems - Yu Zhang; Chengwei He; Yanwen Xiao; Chuanjun Yang; Qian Chen; Xilian Luo; Xin Cui (International Journal of Refrigeration, 2026)

Unraveling the co-evolution of lipidome and flavorome during the light-frying of grass carp cubes: Interactions between lipid oxidation and Maillard reaction - Jinlin Li; Xinwu Hu; Shuanglong Wang; Li Huang; Hanhao Zhou; Chengwei Yu; Mingming Hu; Zongcai Tu; Bizhen Zhong; Bin Peng (Food Chemistry, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

ADAMDEC-1 promotes atherosclerosis progression by interacting with ACTN4 and modulating the PTEN-PI3K/AKT signaling axis - Yanmei Zhang; Chengwei Dai; Lianxin Luo; Yu Gao; Xiaochen Wang (Molecular and Cellular Biochemistry, 2026)

A combined lipidomics and flavoromics approach reveals that enzymatic interesterification improves the flavor stability of stored grass carp (Ctenopharyngodon idella) oil - Bin Peng; Linchuan Xu; Huijuan Zhou; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Food Research International, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Insights into the Characteristics and Mechanism of Heterogeneous In Situ Stress: A Case Study from the YD Copper Mine, China - Jikun Liu; Chenghu Wang; Guiyun Gao; Zengzhen Qian; Shibo Yu; Chengwei Yang; Wei Li (Rock Mechanics and Rock Engineering, 2026)

A critical review of next-generation green scale inhibitors for ultra-deep high-salinity oilfields: From kinetic mechanisms to multifunctional molecular design - Pingli Liu; Chengwei Zuo; Juan Du; Xiang Chen; Jinming Liu; Renyin Zhao; Zhihan Yu; Zhengyou Tang (Desalination, 2026)

Elucidating the Effect of Perilla frutescens Extracts with Various Solvents Treatment on the Physicochemical Properties and Flavor Characteristics of Grass Carp Cubes During Cold Storage - Hao Wang; Chengwei Yu; Yanan Sun; Mengke Tian; Bizhen Zhong; Bin Peng; Mingming Hu; Jinlin Li; Zongcai Tu (Journal of Aquatic Food Product Technology, 2026)

Mapping 25 years of research on gut microbiota and antibiotic resistance: bibliometric insights and future directions - Yiwei Heng; Mengping Wang; Zhen Zhang; Enlin Jian; Chenchen Wu; Chengwei Zhang; Qing Chen; Xiaoping Yu; Yanfeng Zhu; Peiling Cai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Toward clean production of power batteries: An electrode burr detection method fusing line laser scanning and enhanced PointNet++ - Yuedong Sun; Yue Niu; Tianxin Chen; Junjie Chen; Chengwei Hu; Fei Chen; Zihan Zhou; Dawei Li; Yinhua Liu; Guoxin Yu; Yuejiu Zheng (Journal of Cleaner Production, 2026)

Paste-like conductive composites through silver-anchored liquid metal networks with high thermal conductivity and electromagnetic shielding - Chengwei Jiang; Yiqi Xu; Chunfang Zi; Mengwei Tao; Quanshou Feng; Changxiang Hao; Ziyan Yu; Sijin Li; Fangyuan Sun; Haibo Wu; Yuanxin Yan; Liyang Wang; et al. (Chemical Engineering Journal, 2026)

Effects of Different Dietary Protein Source Combinations and Feeding Strategies on the Growth, Digestion, Intestine and Liver Health, and Organoleptic Quality of Large Yellow Croaker (Larimichthys crocea) - Hui Jiang; Peng Qu; Xiaojun Yu; Yuanming Zhang; Linshan Jiang; Chengwei Zhang; Kangsen Mai; Wenbing Zhang (Journal of Ocean University of China, 2026)
The present study investigated the effects of varying protein source combinations and feeding strategies on the growth, health and organoleptic quality of the large yellow croaker ( Larimichthys crocea ). Three iso-nitrogenous and iso-lipidic diets were formulated. The control diet was made with 62% fish meal (FM). The other two experimental diets were formulated by replacing 45% FM with 22.5% mealworm (TM) and 22.5% cottonseed protein concentrate (CPC), or with 22.5% TM and 22.5% Clostridium autoethanogenum protein (CAP), respectively. The three kinds of diet were named as A1, A2 and A3, respectively. Five groups of large yellow croaker were fed with two different strategies: the first three groups were continuously fed with A1, A2 and A3 diets, respectively. The fourth group was alternately fed with A1 and A2 diet every 5 days. The fifth group was alternately fed with A1 and A3 diet every 5 days. The five groups were named D1, D2, D3, D1-2 and D1-3, respectively. Results showed that D2 and D3 groups exhibited significantly lower weight gain rate ( WGR ) and higher feed conversion ratios ( FCR ) compared to the D1 group. The D1-2 and D1-3 groups exhibited improved WGR and significantly reduced FCR compared to the D2 and D3 groups. The A2 and A3 diets significantly suppressed digestive enzymes’ activities compared to A1, whereas alternate-feeding groups significantly enhanced the enzyme activities. Compared to the D1 group, D2 and D3 groups significantly downregulated mRNA expression levels of intestinal anti-inflammatory cytokines and upregulated the expression of pro-inflammatory mediators. The anti-inflammatory abilities in the D1-2 and D1-3 groups were significantly higher than those in the D2 and D3 groups. Additionally, diets containing TM+CAP and TM+CPC protein sources enhanced ventral redness and yellowness indices. Considering the growth, digestion, immunity and organoleptic quality of large yellow croaker, it is recommended to replace up to 45% of FM with TM+CPC and use an alternate-feeding strategy.

Interfacial damage mechanisms in hot-recycled asphalt mixtures: A molecular dynamics study considering the blending level between virgin and aged asphalt - Chengwei Xing; Mingchen Li; Ruihan Yu; Tian Jin; Bohan Zhu (Fuel, 2026)

Analysis of key factors affecting the production of biogenic amines in Xinjiang air-dried beef - Rong Huang; Yutong Bai; Chengwei Liu; Ying Huang; Jianhao Geng; Shiling Lu; Honghong Yu; Jun Liu (Food Bioscience, 2026)

Sustained-release Drug Delivery System of Trazodone Hydrochloride Based on Electrospray Technology: Preparation, Characterization, In vitro and In vivo Evaluation - Chengwei Wang; Haiqiao Wang; Michael Adu-Frimpong; Zhihui Zou; Zhou Jin; Peiqi Lu; Zhenrong Liu; Haojie Tian; Ying Xu; Kailun Yang; Jiangnan Yu; Ximing Xu; et al. (AAPS PharmSciTech, 2025)

Spatio-temporal heterogeneity of quality attributes and flavors in grass carp (Ctenopharyngodon idella) cubes during deep frying: Key metabolic evidence - Hao Wang; Ning Cui; Bin Peng; Chengwei Yu; Bizhen Zhong; Mingming Hu; Jinlin Li; Zongcai Tu (Food Chemistry, 2025)

Influence of froude number on the development and evolution of secondary flows in a sharply curved bend: An experimental and numerical study - Chengwei Hu; Yujiao Liu; Minghui Yu (Advances in Water Resources, 2025)

Dispersion, radiological dose assessment, risk evaluation, and emergency response of radioactive materials based on WRF-HYSPLIT modeling - Hefan Liu; Guiying You; Chengwei Lu; Liquan Ge; Peng Yu (Journal of Environmental Radioactivity, 2025)

The evolutionary relationship between sugar-sweetened beverages and type 2 diabetes mellitus since 1989 - Enlin Jian; Mengping Wang; Zhen Zhang; Chengwei Zhang; Qing Chen; Yiwei Heng; Xiaoping Yu; Yanfeng Zhu; Peiling Cai (Food Research International, 2025)

Identification of ATG18s in Triticeae reveals wheat TaATG18-5′s crucial role in Fusarium crown rot resistance - Meng Zhang; Ming Cheng; Xiaoying Deng; Xiaoxiao Zhang; Guoguo Lv; Yuanyuan Guan; Puwen Song; Yongang Yu; Chunji Liu; Haiyan Hu; Chengwei Li (Plant Cell Reports, 2025)

Carbon black induced fluorination enables robust membrane distillation for landfill leachate treatment - Fangshu Qu; Zhuoran Yi; Qiaoyun Lai; Zhu Xiong; Chengwei Nie; Huarong Yu; Gaosheng Zhang; Shuaifei Zhao (Water Research, 2025)

Application, mechanism and future prospect of electric field in fish processing and preservation: A review - Bin Peng; Huimin Ma; Linchuan Xu; Hanhao Zhou; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Trends in Food Science & Technology, 2025)

Comprehensive lipidomics and flavoromics reveals the accelerated oxidation mechanism of fish oil from silver carp (Hypophthalmichthys molitrix) viscera during heating - Jinlin Li; Junru Bai; Liping Yuan; Huijuan Zhou; Linchuan Xu; Chengwei Yu; Mingming Hu; Zongcai Tu; Bin Peng (Food Chemistry, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

Supercritical water gasification of hyperaccumulators: Study on hydrogen production, heavy metal immobilization, and environmental risk assessment - Chengwei Huang; Shanke Liu; Xu Bao; Jialing Xu; Xuanyu Cai; Chao Liang; Lijun Yu (Journal of Environmental Chemical Engineering, 2025)

Microcystin-LR induces neuronal damage through mitophagy defects resulted from the downregulated transcription of Scd2 by directly targeting IGF-1R - Yao Tan; Yujing Huang; Weiyan Chen; Tingyuan Lang; Lingqiao Wang; Xiaoling Chen; Haili Yu; Zhiqun Qiu; Ke Cui; Chengwei Guo; Yiqi Wang; Ziyuan Zhou (Environmental Pollution, 2025)

The possible inhibition mechanism of low salt dry-curing on volatile flavor deterioration in refrigerated grass carp (Ctenopharyngodon idella) blocks: Metabolomics and microorganisms - Bin Peng; Linju Xu; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Food Chemistry, 2025)

Fe3O4 clusters with high photothermal performance for photothermal therapy of tumor - Renpeng Yang; Xiaogang Yu; Chengxiong Wei; Chengwei Wu; Wei Zhang (Chemical Engineering Journal, 2025)

Interpretable regional meteorological feature extraction enhances deep learning for extended 120-h PM2.5 forecasting - Xinyi Liu; Xueting Pu; Chengwei Lu; Han Zhang; Tao Li; Michael L. Grieneisen; Jucheng Li; Ning Ma; Chang Yan; Yu Zhan; Fumo Yang (Journal of Cleaner Production, 2024)

Heterogenous impact of background meteorological factors on the cooling effect of two types of typical urban parks: Evidence from Shanghai, China - Xiaolei Geng; Dou Zhang; Wei Sun; Yuan Yuan; Chengwei Li; Zhaowu Yu (Building and Environment, 2024)

Formononetin-Loaded Self-Microemulsion Drug Delivery Systems for Improved Solubility and Oral Bioavailability: Fabrication, Characterization, In Vitro and In Vivo Evaluation - Zhihui Zou; Yuanyuan Xue; Michael Adu-Frimpong; ChengWei Wang; Zhou Jin; Ying Xu; Jiangnan Yu; Ximing Xu; Yuan Zhu (AAPS PharmSciTech, 2024)

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

Lipidomics profile and volatile compounds of squids (Illex argentinus, Ommastrephes Bartram and Dosidicus gigas) in the Argentine, North Pacific Ocean, Equator and Peru by UPLC-triple TOF-MS and HS-SPME-GC-O-MS - Bin Peng; Jinlin Li; Chengwei Yu; Mingming Hu; Bizhen Zhong; Shengqi Shi; Zongcai Tu (Food Research International, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Effects of steam explosion on raspberry leaf structure and the release of water-soluble nutrients and phenolics - Zhiyue Wang; Zeyuan Deng; Chengwei Yu; Jianyong Wu; Ting Luo (Food Chemistry, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Imbibition characteristics and mechanisms of coal using digital image subtraction technique based on Micro-CT - Yanbin Yu; Jinhao Wang; Wenting Cui; Chengwei Gao; Yongtao Chen; Zihao Yuan (Fuel, 2024)

The degradation and antioxidant capacity of anthocyanins from eggplant peels in the context of complex food system under thermal processing - Zhiyue Wang; Yanfei Zhang; Zhijun Tu; Chengwei Yu; Rong Liu; Zeyuan Deng; Ting Luo (Food Bioscience, 2024)

Hierarchical molecular sieve-based Ce-Ru oxide for enhanced catalytic oxidation of chlorobenzene: Insight into the synergistic effect of Ce and Ru, the role of molecular sieve - Chengwei Yu; Jia-nan Gu; Yixin Xue; Mingming Guo; Kan Li; Jinping Jia; Tonghua Sun (Process Safety and Environmental Protection, 2024)

KCA/Na2SiO3/PNIPAm hydrogel with highly robust and strong solar modulation capability for thermochromic smart window - Rui Guo; Yuchun Shen; Yu Chen; Cheng Cheng; Chengwei Ye; Shaochun Tang (Chemical Engineering Journal, 2024)

Rational synthesis of 1,3,4-thiadiazole based ESIPT-fluorescent probe for detection of Cu2+ and H2S in herbs, wine and fruits - Yu Sun; Jie Mu; Yongchen Wang; Chengwei Lü; Li-Wei Zou (Analytica Chimica Acta, 2024)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

The toxic mechanism of tetracycline on root tips in hulless barley (Hordeum vulgare L. var. nudum) - Wenxiu Xue; Wenhan Liu; Ruwen Ma; Shuhao Zhang; Xingxu Yu; Tao Li; Xiaoyu Luan; Xiaowei Cui; Jia Liu; Chengwei Zhang; Shaolei Shan; Shouqing Ni; et al. (Journal of Hazardous Materials, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Natural siderite derivatives activated peroxydisulfate toward oxidation of organic contaminant: A green soil remediation strategy - Chengwei Zhong; Yinying Jiang; Quanfeng Liu; Xiaoshuang Sun; Jiang Yu (Journal of Environmental Sciences, 2023)

Integrated metabolomics analysis of Lactobacillus in fermented milk with fish gelatin hydrolysate in different degrees of hydrolysis - Yi Le; Xiaowei Lou; Chengwei Yu; Chenxi Guo; Yun He; Yuyun Lu; Hongshun Yang (Food Chemistry, 2023)

Impacts of climatic zones on urban heat island: Spatiotemporal variations, trends, and drivers in China from 2001–2020 - Xiaolei Geng; Dou Zhang; Chengwei Li; Yuan Yuan; Zhaowu Yu; Xiangrong Wang (Sustainable Cities and Society, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Construction of BiOCl/Ti-MOFs type-II heterojunction photocatalyst for enhanced photocatalytic performance for multiple antibiotics removal - Chengwei Wang; Zhuhuan Chen; Ruobing Yu (Environmental Science and Pollution Research, 2023)

Activation of peroxydisulfate by MIL-101(Fe)/g-C3N4 for 2-chlorophenol–contaminated soil: parameter optimization by response surface methodology - Quanfeng Liu; Jiang Yu; Yinying Jiang; Chengwei Zhong; Senxu Ding; Peng Zhou; Yuanxiao Jin (Journal of Soils and Sediments, 2022)

Study on seepage and wettability distribution of coal seam water injection based on electrical conductivity - Lei Zheng; Dewen Li; Yanbin Yu; Chengwei Gao; Yanpei Guo; Qilin Xin (Arabian Journal of Geosciences, 2022)

Applying modified biochar with nZVI/nFe3O4 to immobilize Pb in contaminated soil - Peirou Li; Jiang Yu; Zhuoxi Huangfu; Jiahua Chang; Chengwei Zhong; Ping Ding (Environmental Science and Pollution Research, 2020)

Development of a high spatiotemporal resolution cloud-type classification approach using Himawari-8 and CloudSat - Chengwei Zhang; Xiaoyong Zhuge; Fan Yu (International Journal of Remote Sensing, 2019)

Silencing of glycerol-3-phosphate acyltransferase 6 (GPAT6) gene using a newly established virus induced gene silencing (VIGS) system in cucumber alleviates autotoxicity mimicked by cinnamic acid (CA) - Ruifang Bu; Runhao Wang; Qichao Wei; Haiyan Hu; Haili Sun; Puwen Song; Yongang Yu; Qili Liu; Zichao Zheng; Tong Li; Dongxiao Li; Lei Wang; et al. (Plant and Soil, 2019)

Soil characteristics and their potential thresholds associated with Scirpus mariqueter distribution on a reclaimed wetland coast - Chengwei Li; Yandong Tao; Meng Zhao; Kefeng Yu; Lingqian Xu; Shubo Fang (Journal of Coastal Conservation, 2018)

Comparative proteomic analysis reveals differential protein and energy metabolisms from two tobacco cultivars in response to cold stress - Risheng Hu; Xianxin Zhu; Shipeng Xiang; Xianwen Zhang; Zhi Liu; Lieshu Zhu; Yu Cao; Chengwei Yang; Jianbin Lai (Acta Physiologiae Plantarum, 2018)

IAA producing Bacillus altitudinis alleviates iron stress in Triticum aestivum L. seedling by both bioleaching of iron and up-regulation of genes encoding ferritins - Zhongke Sun; Kun Liu; Ju Zhang; Yi Zhang; Kedong Xu; Deshui Yu; Jian Wang; Lizong Hu; Long Chen; Chengwei Li (Plant and Soil, 2017)

Isolation and expression analyses of methyl-d-erythritol 4-phosphate (MEP) pathway genes from Haematococcus pluvialis - Chengwei Liang; Wei Zhang; Xiaowen Zhang; Xiao Fan; Dong Xu; Naihao Ye; Zhongliang Su; Jiansheng Yu; Qingli Yang (Journal of Applied Phycology, 2016)

The Expression of HSPD1, SCUBE3, CXCL14 and Its Relations with the Prognosis in Osteosarcoma - Wenqing Liang; Chengwei Yang; Jiahao Peng; Yu Qian; Zirui Wang (Cell Biochemistry and Biophysics, 2015)

Three-dimensional extension of the unit-feature spatial classification method for cloud type - Chengwei Zhang; Fan Yu; Chenxi Wang; Jianyu Yang (Advances in Atmospheric Sciences, 2011)

Development and genetic mapping of SSR markers in foxtail millet [Setaria italica (L.) P. Beauv.] - Xiaoping Jia; Zhongbao Zhang; Yinghui Liu; Chengwei Zhang; Yunsu Shi; Yanchun Song; Tianyu Wang; Yu Li (Theoretical and Applied Genetics, 2009)

Transient expression of lacZ in bombarded unicellular green alga Haematococcus pluvialis - Changying Teng; Song Qin; Jianguo Liu; Daozhan Yu; Chengwei Liang; Chengkui Tseng (Journal of Applied Phycology, 2002)